Pornographic Values: Hierarchy and Hubris. (4th March 2016) - Jensen, Robert
Although the radical feminist critique has been eclipsed by postmodern and liberal positions in the debate over pornography during the past two decades, that radical critique remains the best framework for understanding sexually explicit material. When combined with a critique of the assumptions and values of a hypermediated society, radical feminism helps sharpen our inquiry into what it means to be human at this point in history. The contemporary pornography industry is based on a patriarchal gender fundamentalism and pornographic/media fundamentalism that undermine our ability to achieve self-realization in stable, respectful communities. Public Health Significance Statement: The sexual exploitation of women in pornography and the hypermediated nature of life in the contemporary United States can undermine the ability of people, especially men, to build the relationships needed for stable, respectful human communities.